Characterization of an isolated lactase enzyme produced by Bacillus licheniformis ALSZ2 as a potential pharmaceutical supplement for lactose intolerance - Amin, Alaa A.; Olama, Zakia A.; Ali, Safaa M. (Frontiers in Microbiology, 2023)
Introduction Lactose intolerance is a widespread problem that affects people of many different races all over the world. The following pharmacological supplements can improve the lives of those who suffer from this issue. Methods This work focused on lactase producer isolation and statistical design (Plackett–Burman, and BOX–Behnken) to maximize the effectiveness of environmental factors. A lactase-producing bacterium was chosen from a discovery of 100 strains in soil that had previously been polluted with dairy products. Plackett-Burman investigated fifteen variables. Results The most critical variables that lead to increased lactase synthesis are glucose, peptone, and magnesium sulfate (MgSO4). The ideal process conditions for the creation of lactase yield among the stated variables were then determined using a BOX-Benken design. To establish a polynomial quadratic relationship between the three variables and lactase activity, the Box–Behnken design level was used. The EXCEL-solver nonlinear optimization technique was used to predict the best form for lactase production. The ideal temperature and pH levels have been determined, both before and after the lactase purification process, to achieve the highest performance of isolated lactase. Conclusion According to this study, Bacillus licheniformis is a perfect supply of the lactase enzyme (β -Galactosidase), It can be used as a product to assist people who have health issues due to lactose intolerance.